Natorp: reflection (and every subjective act) objectifies, so the subject as such eludes it. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Natorp: reflection (and every subjective act) objectifies, so the subject as such eludes it.
iso-id: iso:argument:GzwkoxQI; sha256: sha256:601d5c7b8771f2e0418db558017ba6dbff4bf84b449193b883d934ff4be4c1a8